Efektivitas Model Pembelajaran Discovery Learning Berbantuan Media Power Point Dalam Meningkatkan Kompetensi Guru Pendidikan Agama Islam - Izalmianto Izalmianto; Iskandar Iskandar; Ahmad Ridwan (SOKO GURU: Jurnal Ilmu Pendidikan, 2026)
This research was motivated by the discovery of several issues related to teacher competency that can impact the quality of education. Among the teachers at Public Elementary School 061/VII Bukit Talang Mas, it was found that some teachers still use conventional learning models, such as extensive lecture methods. They have not yet adopted technology-based methods. Teacher competency remains weak, especially in professional competency, and students are still unable to master the expected competencies. This study aims to determine and analyze the process of using the PowerPoint-assisted discovery learning model to improve the competency of Islamic Religious Education (PAI) teachers. Data collection techniques used were observation, interviews, and documentation, with purposive sampling. The results of this study indicate: The application of the PowerPoint-assisted discovery learning model improves Islamic Religious Education (PAI) learning in terms of effective planning, by implementing syntactic stimulation, problem statements, data collection, data processing, verification, and generalization. In terms of the implementation of the process, students appear more active in asking questions, discussing, and expressing opinions compared to conventional learning. Supporting factors for the implementation of the Discovery Learning Model include teacher competency and readiness, availability of facilities and infrastructure, student characteristics and motivation, and school policy support. Factors Inhibiting the Implementation of the Discovery Learning Model include limited learning time, differences in student abilities, technical constraints, limited mastery of technology and classroom management, monitoring and evaluation, building an academic culture and collaboration, and motivation and appreciation. Efforts made by school principals to effectively implement the Discovery Learning model include policies and program support, competency development, and provision of facilities and infrastructure.